Empowerment in Supporting Community Welfare Through the Vania Bakery Home Industry in Temputejo Village, Blora Regency - Saestika Amelia Putri; Ilyas (Journal of Practice Learning and Educational Development, 2026)
High unemployment rates and limited job opportunities are now major problems that have an impact on the decline in the economic welfare of the community. One of the efforts to overcome this problem is through community empowerment based on small businesses such as home industries. This study aims to analyze the process of community empowerment and its impact on improving economic welfare through the Vania Bakery home industry in Tempurejo Village, Blora Regency. The research method used is a qualitative approach with field research. Data collection was carried out through observation, interviews, and documentation. The results show that the empowerment process of home industry at Vania Bakery takes place in three stages, namely enabling, empowering, and protecting. The training in production, packaging, and marketing skills provided was able to improve the workers' work skills, independence, and income. The existence of this home industry has a positive impact on the community in the form of improved family economic welfare and the creation of a supportive work environment. Thus, Vania Bakery Home Industry plays an important role as a means of community empowerment in helping to improve economic welfare.